PENERAPAN PENDEKATAN ACTIVE LEARNING TIPE SMALL GROUP WORK UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD INPRES 12/79 CELLU - Sitti Jauhar; Sridayanti; Mujahidah; Sudarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This research is a Classroom Action Research (CAR) which aims to describe the improvement in social studies learning outcomes for the 5th Grade of students at SD Inpres 12/79 Cellu, Tanete Riattang Timur District, Bone Regency by applying the Small Group Type Active Learning approach. The focus of this research is the application of the Small Group Work Active Learning approach and the improvement of social studies learning outcomes. The setting for this research was SD Inpres 12/79 Cellu, Tanete Riattang Timur sub-district, Bone district. The subjects of this study were all of 17 students of the 5th Grade, and the homeroom teacher of the 5th Grade. The data collection techniques used were observation, testing and documentation. The data analysis technique used is a quantitative descriptive. The results showed that there was an increase, both in teacher and student activities and learning outcomes in social studies subjects from cycle I with Enough qualifications and in the cycle II increased to Good qualifications. Conclusion: the application of the Small Group Work Type of Active Learning approach can improve social studies learning outcomes for the 5th Grade students of SD Inpres 12/79 Cellu, Tanete Riattang Timur sub-district, Bone district.